Viruses agents of evolutionary invention - Cordingley, Michael G., 1958- (Harvard University Press, 2017)
Viruses are the most abundant biological entities on Earth, and arguably the most successful. They are not technically alive, but--as infectious vehicles of genetic information--they have a remarkable capacity to invade, replicate, and evolve within living cells. Synthesizing a large body of recent research, Michael Cordingley goes beyond our familiarity with viral infections to show how viruses spur evolutionary change in their hosts, shape global ecosystems, and influence every domain of life. In the past few decades, research has revealed that viruses are fundamental to the photosynthetic capacity of the world's oceans and the composition of the human microbiome. Perhaps most fascinating, viruses are now recognized as remarkable engines of the genetic innovation that fuels natural selection and catalyzes evolution in all domains of life. Viruses have coevolved with their hosts since the beginning of life on our planet and are part of the evolutionary legacy of every species that has ever lived. Cordingley explains how viruses are responsible for the creation of many feared bacterial diseases and the emergence of newly pathogenic and drug-resistant strains. And as more and more viruses jump to humans from other animals, new epidemics of viral disease will threaten global society. But Cordingley shows that we can adapt, relying on our evolved cognitive and cultural capacities to limit the consequences of viral infections.--